The W. Chan Kim and Renée Mauborgne Blue Ocean Strategy Reader : the iconic articles by bestselling authors W. Chan Kim and Renée Mauborgne. - Kim, W. Chan.; Mauborgne, Renée A. (Boston : Harvard Business Review Press, 2017)
The seminal book "Blue Ocean Strategy" has sold over 3.5 million copies globally and is in print in forty-three different languages. But much of W. Chan Kim and Renée Mauborgne's work on creating new market spaces was originally published in the pages of Harvard Business Review. This book brings the best of those articles together all in one place. Piece by piece, these articles explain the process of focusing on noncustomers and creating "blue oceans": uncontested market spaces, untainted by competition. They also introduce tools for exploring and exploiting these markets, such as the Strategy Canvas, the Six Paths Framework, the Four Actions Framework, the Pioneer-Migrator-Settler Map, the Buyer Utility Map, the Price Corridor of the Mass, and the Business Model Guide--the tools that have come to make up the Blue Ocean Strategy framework. This collection also features Kim and Mauborgne's latest Harvard Business Review article, "Red Ocean Traps." Whether or not you're familiar with Blue Ocean Strategy, this book will give you another perspective onto this widely accepted framework--and help you implement it in your organization.--
Value innovation: the strategic logic of high growth -- Fair process: managing in the knowledge economy -- Creating new market space -- Knowing a winning business idea when you see one -- Charting your company's future -- Tipping point leadership -- Blue ocean strategy -- How strategy shapes structure -- Blue ocean leadership -- Red ocean traps: the mental models that undermine market-creating strategies.
Print version record.
Master record variable field(s) change: 072, 650 - OCLC control number change
Keywords: Market segmentation; New products; Market segmentation; Market segmentation; New products; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books